Assessment of Beta-2 Microglobulin Gene Edited Airway Epithelial Stem Cells as a treatment for Sulfur Mustard Inhalation - Naeimi Kararoudi, Meisam; Alsudayri, Alfahdah; Hill, Cynthia L.; Elmas, Ezgi; Sezgin, Yasemin; Thakkar, Aarohi; Hester, Mark E.; Malleske, Daniel T.; Lee, Dean A.; Neal, Matthew L.; Perry, Mark R.; Harvilchuck, Jill A.; et al. (Frontiers in Genome Editing, 2022)
Respiratory system damage is the primary cause of mortality in individuals who are exposed to vesicating agents including sulfur mustard (SM). Despite these devastating health complications, there are no fielded therapeutics that are specific for such injuries. Previous studies reported that SM inhalation depleted the tracheobronchial airway epithelial stem cell (TSC) pool and supported the hypothesis, TSC replacement will restore airway epithelial integrity and improve health outcomes for SM-exposed individuals. TSC express Major Histocompatibility Complex (MHC-1) transplantation antigens which increases the chance that allogeneic TSC will be rejected by the patient’s immune system. However, previous studies reported that Beta-2 microglobulin (B2M) knockout cells lacked cell surface MHC-1 and suggested that B2M knockout TSC would be tolerated as an allogeneic graft. This study used a Cas9 ribonucleoprotein (RNP) to generate B2M-knockout TSC, which are termed Universal Donor Stem Cells (UDSC). Whole genome sequencing identified few off-target modifications and demonstrated the specificity of the RNP approach. Functional assays demonstrated that UDSC retained their ability to self-renew and undergo multilineage differentiation. A preclinical model of SM inhalation was used to test UDSC efficacy and identify any treatment-associated adverse events. Adult male Sprague-Dawley rats were administered an inhaled dose of 0.8 mg/kg SM vapor which is the inhaled LD50 on day 28 post-challenge. On recovery day 2, vehicle or allogeneic Fisher rat UDSC were delivered intravenously (n=30/group). Clinical parameters were recorded daily, and planned euthanasia occurred on post-challenge days 7, 14, and 28. The vehicle and UDSC treatment groups exhibited similar outcomes including survival and a lack of adverse events. These studies establish a baseline which can be used to further develop UDSC as a treatment for SM-induced airway disease.